Towards architectural design empowerment: an analysis of the Solidary Mobile Housing project's development process through Theory of Action in Direct Design Empowerment Framework - De Smet, Aurelie; Kesdi, Hatice Server; Pak, Burak (CoDesign, 2025)
While many design projects assume they empower participants, studies that evaluate the effectiveness of empowerment in Participatory Design (PD) are rare. This paper investigates which elements architectural design projects need to consider if they want to effectively empower the individuals and communities involved. To address this, we use the Theory of Action (ToA) part of the Direct Design Empowerment Framework, to analyse the end user empowerment process and outcomes in the Solidary Mobile Housing (SMH) project and draw lessons from this case. SMH is a Living Laboratory on the co-creation of an alternative, temporary, or transitional housing solution for the Brussels-Capital Region. Our detailed unravelling of the inputs, strategies, activities, factors, outcomes, and outputs of this PD project reveals how consideration of all participants' needs and wishes, collaboration with experienced social organisations, the use of boundary objects, and extensive and open communication not only contributed to empowering the homeless people involved but also led to mutual learning for all the other parties involved. In general, this paper demonstrates how participation in the design process can enable signposting/prefiguration directly with end users and allow for Networked Critical Spatial Practices and how this, in turn, can contribute to architectural design empowerment.